Crime and economic activity. A panel data approach - Witt, Robert (The British journal of criminology, 1999)
We use aggregate data from 42 police force areas to examine the relationship between economic factors and property crime. The change in unemployment is seen to impact positively on four types of criminal activity examined. A widening of the distribution of weekly earnings of full-time manual men (a measure of wage inequality) and increases in cars per capita (a measure of the availability of thievable property) lead to increases in crime. We also find evidence that increases in the size of the police force reduce property crime